cos(pi/12)=sqrt(2+sqrt(3))/2
sin(pi/12)=sqrt(2-sqrt(3))/2
cos(pi/8)=sqrt(2+sqrt(2))/2
sin(pi/8)=sqrt(2-sqrt(2))/2
so
P_1=(-3sqrt(2+sqrt(3));-3sqrt(2-sqrt(3)))
P_2=(-3/2sqrt(2+sqrt(2));3/2sqrt(2-sqrt(2)))
bar(P_1P_2)=sqrt((-3sqrt(2+sqrt(3))+3/2sqrt(2+sqrt(2)))^2+(3sqrt(2-sqrt(3))+3/2sqrt(2-sqrt(2)))^2)=
=sqrt(18+cancel(9sqrt3)+9/2+cancel(9/4sqrt2)-9sqrt((2+sqrt3)(2+sqrt2))+18-cancel(9sqrt3)+9/2-cancel(9/4sqrt2)+9sqrt((2-sqrt2)(2-sqrt3)))=
=sqrt(45-9(sqrt(4+sqrt6+2(sqrt2+sqrt3))-sqrt(4+sqrt6-2(sqrt2+sqrt3))))
=3sqrt(5-(sqrt(4+sqrt6+2sqrt(5+2sqrt6))-sqrt(4+sqrt6-2sqrt(5+2sqrt6))))
Now put
a=8+2sqrt(6)
and
b=8
then
a^2-b=80+32sqrt(6)
so using
sqrt(a-sqrtb)=sqrt((a+sqrt(a^2-b))/2)-sqrt((a+sqrt(a^2-b))/2)
sqrt(8+2sqrt(6)-sqrt(8))=
=sqrt((8+2sqrt(6)+4sqrt(5+2sqrt6))/2)-sqrt((8+2sqrt(6)-4sqrt(5+2sqrt6))/2)
=sqrt(4+sqrt(6)+2sqrt(5+2sqrt6))-sqrt(4+sqrt(6)-2sqrt(5+2sqrt6))
So
bar(P_1P_2)=3sqrt(5-sqrt(8+2sqrt(6)-sqrt(8)))=3sqrt(5-sqrt(8+2(sqrt(6)-sqrt(2))))